CHOOSING ACCEPTABLE PARAMETERS FOR EXPERIMENT ON NEW ENERGY-SAVING VACUUM SUBLIMATION DRYING EQUIPMENT - Egamberdiyev, Azizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. The purpose of the project was to increase the capacity of our country on fruit and vegetable expositions, to research drying devices in order to increase their economic efficiency by reducing the energy consumption of existing devices, to create a new energy-saving vacuum sublimation drying device and to improve the technological process regimes. Methods. In carrying out the study, methods of collecting data on the subject, studying national and foreign experience, systematic analysis of literature, generalization and recording of practical results were used. Results. In this article, the optimal parameters for experimenting with a new energy-efficient, improved vacuum sublimation drying equipment developed by researchers are reflected. Conclusion. The analysis of the data obtained shows that the total energy and operational costs in the sublimation drying method are higher than in other drying methods (except for dielectric drying). Therefore, this method of drying is used for drying materials (meat, fruits, vegetables, medicine and pharmaceutical products), which are valuable substances, resistant to high temperatures and whose biological properties must be preserved for a long period of time. But in this process, the product retains almost 98% of vitamins in itself, and its appearance practically does not change.